The Impact of Load Variability on Data Center Infrastructure: Quantifying Resilience and Operational Risk - Nur Aisyah Ramli Nur Aisyah Ramli; Muhammad Fikri Hasan Muhammad Fikri Hasan (Techne: Journal of Engineering, Technology and Industrial Applications, 2025)
This article presents an applied reliability engineering framework for data center operations that quantifies cooling resilience, power quality stability, and uptime risk using measurable operational indicators rather than purely qualitative compliance checklists. The framework models thermal risk through time-to-threshold metrics derived from rack inlet temperatures, airflow margin indicators, and cooling response latency, while power risk is modeled using voltage and frequency quality statistics, transient event rates, and uninterruptible power supply (UPS) stress indicators. A generic case-based evaluation demonstrates how normal load variability and maintenance switching events shift the distributions of thermal and electrical indicators, and how risk-based governance can reduce nuisance alarms while improving early detection of conditions that precede service-impacting incidents. Results show that the most common reliability bottleneck is not total capacity, but degraded margin caused by uneven airflow distribution, partial containment failures, and localized hot spots, and that power disturbances primarily elevate risk when combined with reduced thermal margin or when UPS response is delayed by maintenance states. The paper provides copy-ready tables for operational KPI reporting, along with prompts for scientific figures suitable for Techne publication, and concludes with implementation guidance for alarm governance, preventive maintenance scheduling, and integrated power-thermal risk management.